(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It was required to build an overhead water tank under “ Hargharnaljal Scheme” in Purusottampur in Surguja C.G. but the subgrade soil at the location was very unstable so we decided to perform soil stabilization by Lime to increase the stability of soil to retain the load of overhead water tank. By adding the lime to the soil will improves the properties such as stability impermeability and load carrying capacity of the subgrade. It is seen by the recent studies that the lime highly stabilizes the soil instability so we performed the test to get the optimum lime content for soil stabilization and thus improve the soil standard of the place.